Innovation: ice cream in the recovery room rules out chylothorax after thoracic lymphadenectomy and affords same-day chest tube removal - Cerfolio, Robert J.; McCormack, Ashley J. (Frontiers in Surgery, 2024)
Early removal of chest tubes reduces pain and morbidity. The aim of this study was to remove chest tubes as soon as possible after robotic pulmonary resection with complete thoracic lymphadenectomy by administering ice cream to rule out chylothorax.This is a quality improvement study of prospectively gathered data from one thoracic surgeon.Patients were given 3.6 fl oz of ice cream in the recovery room within one hour after the completion of their operation. Chest tubes were removed within 4 hours if there was no chylous drainage and there was no air leak on the digital drainage system.From January 2022 until August 2023, 343 patients underwent robotic pulmonary resection with complete thoracic lymphadenectomy. Median time to ingest the ice cream was 1.5 hours after skin closure. The incidence of chylothorax was 0.87% (3/343). Two patients were diagnosed with a chylothorax after eating ice cream within four hours of surgery. One patient whose chest tube remained for an air leak had a chylothorax diagnosed on postoperative day 1 (POD1). All three patients went home on POD1 with their chest tube in place on a no fat, medium chain triglycerides diet. All chylothoraces resolved within six days. Of the remaining patients, none had a chylothorax diagnosed at any time postoperatively with a minimum of 90-day follow-up.Providing ice cream to patients after pulmonary resection and complete thoracic lymphadenectomy is an effective and reliable technique to rule out chylothorax early in the postoperative period and